Web-Based Intelligent Tutoring System On Students Achievement And Interest In Technical Drawing In Niger State - Hassan, Abdullahi Muhammad; Usman; Bala; Mannir; Karfe (Journal of Information Systems and Technology Research, 2023)
The study examines how a web-based innovative coaching system affects students' performance and interest in technical drawing in Niger, Nigeria. The hypotheses created in answer to the two study questions are evaluated using the A.05 significance threshold. The investigation was conducted utilizing a pre-post non-equivalent control group quasi-experimental study design. The study's participants comprised 428 National Technical College (NTC) II, students. The sample size for this study was 180 students, of whom 68 were in the experimental group, and 112 were in the control group. The experimental group employed Simple Random Sampling (SRS) and intentional sampling techniques. The instruments used to gather data are the Technical Drawing Achievement Test (TDAT) and the Technical Drawing Interest Inventory (TDII). The reliability coefficient for TDAT is 0.77, whereas the reliability coefficient for TDII is 0.79 using the Pearson Product Moment Correlation coefficient. The mean was used to answer research questions, and ANCOVA was used to evaluate the hypotheses. The study's findings demonstrated that web-based intelligent tutoring solutions are more successful in raising student achievement and piquing their interest in technical drawing than traditional teaching techniques. It was suggested that professors, particularly those teaching technical drawing, employ a web-based intelligent tutoring system for technical college students to enhance students' academic performance and pique their interest in technical drawing.